C-reactive protein concentration as a guide to antibiotic therapy in acute leukaemia. - Schofield, K P (1982)
Serial monitoring of the serum C-reactive protein (CRP) concentration was performed, using a one-hour laser-immunonephelometric assay, during 29 episodes of infection in 22 neutropenic patients with acute leukaemia. Serum CRP increased to above a diagnostic level of 100 mg/l in all 29 episodes and continued to rise progressively until appropriate antibiotics, or granulocytes, were given when it fell with a half-life of approximately three days. Serial study of the serum concentration was of value in detecting occult or unresolved bacterial infection and provided an objective means of monitoring the response to antibiotic and granulocyte therapy.